The Middle East and Palestine
256 p.
Keywords: Taking issue with the convenient views that the Middle East is an irrational and exceptional region of world politics, and that the long and bloody history of the Palestine conflict is proof, the authors combine theoretical reflection and empirical investigation, marrying International Relations theory and Middle East area studies. Through integrating macro and micro-perspectives, tracing the interaction of global and regional environments with individuals pursuing political goals, this book rejects the cultural stereotype of 'Middle Eastern exceptionalism' and argues that regional patterns of conflict are deeply embedded in international and transnational relations, and that their particular trajectories have to be interpreted in light of global political developments.